Raw material powder for preparing high-thermal-conductivity silicon nitride ceramic as well as preparation method and application of raw material powder

By using silicon nitride and zirconium oxide grinding balls in the preparation of silicon nitride ceramic powder for combined ball milling and adding zirconium oxide chips, the existing silicon nitride ceramics have been solved, and high thermal conductivity, excellent mechanical properties and low-cost prepared silicon nitride ceramic materials are achieved.

CN119551992APending Publication Date: 2025-03-04TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI +1

Patent Information

Application Number
CN202311126835.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The thermal conductivity of existing silicon nitride ceramic materials is low, and the use of silicon nitride grinding balls in powder preparation is low efficiency and cost.

Method used

Combined ball milling is performed by silicon nitride grinding balls and zirconia grinding balls. By controlling the particle size and proportion of the grinding balls, the ball milling efficiency is improved and the cost is reduced. At the same time, zirconia debris is incorporated during the ball milling process to improve the density and thermal conductivity of the ceramic.

Benefits of technology

The thermal conductivity of silicon nitride ceramics is significantly improved, its relative density and overall density are enhanced, while maintaining high bending strength and fracture toughness, reducing preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119551992A_ABST
    Figure CN119551992A_ABST
Patent Text Reader

Abstract

The invention discloses raw material powder for preparing high-thermal-conductivity silicon nitride ceramic as well as a preparation method and application of the raw material powder. The raw material powder comprises silicon nitride powder; a sintering aid; and zirconium oxide chips falling off from the zirconium oxide grinding ball when the zirconium oxide grinding ball and the silicon nitride grinding ball are used for grinding. The trace doping of zirconium oxide promotes the densification of the silicon nitride ceramic and improves the relative density and the overall density on one hand, and on the other hand, zirconium oxide is mainly distributed in a triangular grain boundary position in a dispersed phase manner and is not dissolved in a silicon nitride grain lattice, so that the thickness of an intergranular phase is not increased, and the thickness of the silicon nitride is increased. The thermal conductivity of the finally obtained silicon nitride ceramic material is more than 100W / (m.K).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of silicon nitride ceramic synthesis, and more specifically, to a raw material powder for preparing high thermal conductivity silicon nitride ceramics, and a preparation method and application thereof. Background Art

[0002] In recent years, with the continuous development of integrated circuits, the number of semiconductor chips, circuits and packaging density installed on electronic devices has continued to increase, and the problem of device failure caused by heat has become increasingly serious. Studies have shown that thermal failure accounts for more than half of the causes of failure of electronic products. Therefore, improving the thermal conductivity of heat-dissipating ceramic substrates in integrated circuits has become a hot issue of concern to researchers.

[0003] Silicon nitride is a material with excellent properties such as high strength, good toughness, heat shock resistance, corrosion resistance and wear resistance. Silicon nitride ceramics are considered to be the best semiconductor insulating substrate materials with both high strength and high thermal conductivity, and have great market prospects in the application of high-power semiconductor device substrates. Haggerty et al. once predicted that the theoretical thermal conductivity of silicon nitride ceramics can reach 200-320W / (m·K). However, the actual prepared silicon nitride ceramics reported so far are not satisfactory in terms of thermal conductivity. Very few can reach more than 100W / (m·K), which is far below the theoretical value. CN111196727A discloses a high thermal conductivity silicon nitride ceramic material, which regulates the liquid phase composition by providing a low-temperature sintering aid system, hinders the solid solution of oxygen into the silicon nitride lattice, reduces defects in the silicon nitride lattice, reduces the scattering of phonons, and thus improves the thermal conductivity of the material, so that the thermal conductivity of the final silicon nitride ceramic material can reach 78.9W / (m·K). CN108863395B discloses a high thermal conductivity and high strength silicon nitride ceramic material. By adding sintering aids HfO2, HfN or ZrN, sufficient liquid phase is provided to make the grain development more perfect, thereby effectively improving the thermal conductivity of silicon nitride ceramics. The thermal conductivity of the obtained silicon nitride ceramic material can only be up to about 100W / (m·K), and the thermal conductivity is still relatively low. In the current powder raw material preparation process, in order to reduce impurity pollution and improve the powder quality, silicon nitride grinding balls are usually used to refine the powder before sintering. However, the efficiency of grinding with silicon nitride grinding balls is low. At the same time, as a grinding consumable, its expensive price also greatly increases the powder preparation cost.

[0004] Therefore, there is an urgent need to develop a low-cost, easy-to-operate method for preparing high thermal conductivity silicon nitride ceramic materials. Summary of the invention

[0005] Based on the above defects, the first object of the present invention is to provide a raw material powder for preparing high thermal conductivity silicon nitride ceramics. A trace amount of zirconium oxide chips is added to the raw material powder, which promotes the densification of silicon nitride ceramics, improves the relative density and overall density of silicon nitride ceramics, thereby improving the thermal diffusion coefficient and enhancing the thermal conductivity of silicon nitride ceramic materials.

[0006] The second object of the present invention is to provide a method for preparing the raw material powder as described above. The method uses silicon nitride grinding balls with a lower density and zirconium oxide grinding balls with a higher density for combined ball milling, which not only improves the ball milling efficiency but also reduces the preparation cost.

[0007] The third object of the present invention is to provide a high thermal conductivity silicon nitride ceramic, which has high thermal conductivity and can maintain high bending strength and fracture toughness.

[0008] A fourth object of the present invention is to provide an application of the high thermal conductivity silicon nitride ceramic as described above in the preparation of a thermally conductive material.

[0009] In order to achieve the above first object, the present invention adopts the following technical scheme:

[0010] The invention discloses a raw material powder for preparing high thermal conductivity silicon nitride ceramics, the raw material powder comprising

[0011] Silicon nitride powder;

[0012] Sintering aids; and

[0013] Zirconia chips that fall off from zirconia grinding balls when grinding with zirconia grinding balls and silicon nitride grinding balls.

[0014] Furthermore, the particle size of the raw material powder is in the range of 0.5-0.8 μm.

[0015] In order to achieve the above second purpose, the present invention adopts the following technical solutions:

[0016] The present invention discloses a method for preparing the raw material powder as described above, comprising the following steps:

[0017] The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder;

[0018] Add the premixed powder into a ball mill containing grinding balls and grind to obtain the product;

[0019] The grinding balls are composed of silicon nitride grinding balls and zirconium oxide grinding balls, wherein the content of zirconium oxide grinding balls in the grinding balls is 30-60wt%, and the content of silicon nitride grinding balls is 40-70wt%;

[0020] During the ball milling process, zirconia chips that fall off the zirconia grinding balls are incorporated into the premixed powder.

[0021] In the early stage of the research of the present invention, mainly in order to solve the problems of low ball milling efficiency and high cost of silicon nitride grinding balls, zirconia grinding balls with high density and low cost were selected to replace part of the silicon nitride grinding balls to solve the above problems. It was found that after the combined ball milling of the silicon nitride grinding balls with higher density and the zirconia grinding balls with higher density, the ball milling efficiency was effectively improved, and the time required for grinding the unit mass of powder to the target particle size was shortened. Later, with the deepening of the research, it was found that the zirconia debris falling off the zirconia grinding balls would be mixed into the silicon nitride ceramic raw material powder, and the zirconia was mainly distributed in the triangular grain boundary position in the dispersed phase. This not only does not affect the sintering activity of the powder after grinding and the quality of silicon nitride ceramics, but also is beneficial to improve the relative density and overall density of silicon nitride ceramics, thereby improving the thermal diffusion coefficient and enhancing the thermal conductivity of silicon nitride ceramics.

[0022] In the process of calculating the thermal conductivity of the material, three parameters, namely, specific heat, thermal diffusion coefficient and density, are needed. Specific heat is a constant value related to the type of material. After the raw material is selected, its specific heat is determined. Therefore, in improving the thermal conductivity of the material, thermal diffusion coefficient and density become key parameters. Thermal diffusion coefficient can be achieved by increasing relative density and reducing crystal defects and intergranular phase content. Therefore, the most effective means to improve thermal conductivity is to promote densification and reduce the content of lattice defect oxygen. In the present invention, it is precisely because the addition of zirconium oxide debris during the ball milling process increases the relative density and density of the material, promotes material densification, and does not affect lattice oxygen. Moreover, zirconium oxide is mainly distributed in the triangular grain boundary position as a dispersed phase and is not dissolved in the silicon nitride grain lattice. Since it is not at the grain boundary between two particles, it will not cause the thickness of the intergranular phase to increase, and the distribution position will not have a negative impact on thermal conductivity. Therefore, the thermal conductivity of silicon nitride ceramics will be improved overall.

[0023] The added zirconia debris is brought in during the ball milling process due to the shedding of zirconia grinding ball components. The detached zirconia powder is smaller and is mixed with the premixed powder more evenly step by step during the entire ball milling process. This can ensure the uniformity of the distribution of zirconia and premixed powder, which is essentially different from directly adding zirconia powder with the same doping amount. Judging from the current technical level, it is difficult to achieve a considerable degree of uniform dispersion by directly adding zirconia.

[0024] Furthermore, the amount of zirconium oxide that falls off the zirconia grinding balls is very small. According to the inventors' extensive experimental summary, the inventors used the control variable method to establish a curve of the content of zirconium oxide debris added-grinding time by fixing the content ratio of the zirconium oxide grinding balls in the grinding balls, and a curve of the content of zirconium oxide debris added-content ratio of the zirconium oxide grinding balls in the grinding balls by fixing the grinding time. The obtained curves were extracted with data points and fitted in three-dimensional coordinate axes. It was found that the mass percentage of zirconium oxide debris added to the premixed powder due to ball milling, the ball milling time, and the content ratio of the zirconium oxide grinding balls in the grinding balls satisfied the following relationship: a≥0.02x+ln(t-0.8);

[0025] Wherein, a is the mass percentage of zirconia debris added to the premixed powder due to ball milling, x is the content percentage of zirconia grinding balls in the grinding balls, and t is the ball milling time in h.

[0026] Furthermore, the particle size of the zirconium oxide grinding balls is 0.5-12 mm, and the particle size of the silicon nitride grinding balls is 1-4 mm.

[0027] Furthermore, the particle size of the silicon nitride powder is in the range of 5-7 μm, and the particle size of the sintering aid is in the range of 0.1-1.0 μm.

[0028] Furthermore, the silicon nitride powder in the premixed powder accounts for 85-95wt%, the sintering aid accounts for 5-15wt%, and the total mass percentage of the silicon nitride powder and the sintering aid is 100wt%; the mass ratio of the grinding ball to the premixed powder is 1-4:1.

[0029] Furthermore, when selecting sintering aids, the sintering aids commonly used by technicians in this field can be applied to the present invention, and the sintering aids include but are not limited to one or more of Y2O3, Sc2O3, Sm2O3, Lu2O3, Er2O3, MgO, Mg2Si and MgSiN2.

[0030] In order to achieve the third object, the present invention adopts the following technical solutions:

[0031] The invention discloses a high thermal conductivity silicon nitride ceramic, which is prepared by sintering the raw material powder as described above; wherein in the silicon nitride ceramic, zirconium oxide is distributed in the triangular grain boundary position of silicon nitride in the form of dispersed phase.

[0032] Furthermore, the sintering includes but is not limited to one of hot pressing sintering, gas pressure sintering, normal pressure protective atmosphere sintering, and microwave heating sintering.

[0033] Furthermore, the relative density of the silicon nitride ceramic is ≥98%, and the overall density is 3.20-3.31 g / cm 3, thermal conductivity is 100-120W / (m·K), bending strength is 500-780MPa, fracture toughness is 6.0-8.5MPa·m 1 / 2 .

[0034] In order to achieve the fourth objective, the present invention adopts the following technical solutions:

[0035] The present invention discloses an application of the high thermal conductivity silicon nitride ceramics described above in preparing a thermally conductive material.

[0036] The beneficial effects of the present invention are as follows:

[0037] The present invention discloses a raw material powder for preparing high thermal conductivity silicon nitride ceramics, a preparation method and an application thereof. When preparing the raw material powder of silicon nitride ceramics, silicon nitride grinding balls and zirconium oxide grinding balls are used for combined ball milling. By controlling the particle size and proportion of the silicon nitride grinding balls and the zirconium oxide grinding balls, not only the ball milling efficiency is improved and the preparation cost is reduced, but also a trace amount of zirconium oxide falling off the zirconium oxide grinding balls during the ball milling process is added to the premixed powder, which promotes the densification of the silicon nitride ceramics obtained by sintering, improves the relative density and the overall density, and at the same time, enhances the thermal conductivity of the silicon nitride ceramics.

[0038] The obtained silicon nitride ceramic material has high thermal conductivity, bending strength and fracture toughness. The thermal conductivity of all the silicon nitride ceramic materials prepared by testing is greater than 100W / (m·K), the bending strength is not less than 500MPa, and the fracture toughness is not less than 6.0MPa·m 1 / 2 , ensuring that under high thermal conductivity conditions, the bending strength and fracture toughness of the material are not affected. At the same time, the relative density of the silicon nitride ceramic material is relatively high, reaching more than 98%. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.

[0040] Figure 1 The microscopic morphology of the raw material powder in Example 1 is shown.

[0041] Figure 2 The polished surface morphology of the high thermal conductivity silicon nitride ceramic prepared in Example 1 is shown. DETAILED DESCRIPTION

[0042] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0043] Example 1

[0044] The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder;

[0045] The premixed powder is added into a ball mill jar equipped with grinding balls, ball-milled to obtain raw material powder, and sintered to obtain silicon nitride ceramic material.

[0046] Among them, by mass percentage, the silicon nitride grinding balls account for 70wt% of the grinding balls, the zirconium oxide grinding balls account for 30wt%, the diameter of the zirconium oxide grinding balls is 2mm, the diameter of the silicon nitride grinding balls is 2mm, and the grinding time is 2h.

[0047] The silicon nitride powder accounts for 95wt% of the premixed powder, the sintering aid accounts for 5wt%, and the mass ratio of the grinding ball to the premixed powder is 4:1.

[0048] The particle size of the silicon nitride powder is 5 μm, and the particle size of the sintering aid is 0.1 μm.

[0049] The particle size range of the raw powder is 0.80 μm.

[0050] The sintering aids are Y2O3 and MgSiN2, the mass ratio of Y2O3 and MgSiN2 is 5:2, and the sintering conditions are: gas pressure sintering at 1850°C and 1MPa N2 pressure for 4h.

[0051] The relative density of the obtained silicon nitride ceramic material is ≥98.5%, and the overall density is 3.23g / cm 3 , thermal conductivity is 103W / (m·K), bending strength is 658MPa, fracture toughness is 7.1MPa·m 1 / 2 .

[0052] Figure 1 The microscopic morphology of the raw material powder in Example 1 is shown. It can be seen that the raw material powder particles after grinding are equiaxed, the particle size distribution is uniform without abnormally large particles, and the particle size is less than 1 μm.

[0053] Figure 2 The polished surface morphology of the high thermal conductivity silicon nitride ceramic prepared in Example 1 is shown. From the microscopic morphology of the polished surface, it can be seen that the zirconium oxide with high brightness is dispersed at the triangular grain boundaries and is not dissolved in the silicon nitride grain lattice. At the same time, since it is not at the grain boundary between two particles, it will not cause the thickness of the intercrystalline phase to increase, so the existence position has no negative impact on the thermal conductivity; there are no obvious pores on the polished surface of the sintered ceramic, the particles are well developed, and have a bimodal distribution characteristic of long rods and equiaxed small particles. The intercrystalline phases between the particles are mostly at the triangular grain boundaries.

[0054] Example 2

[0055] The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder;

[0056] The premixed powder is added into a ball mill jar equipped with grinding balls, ball-milled to obtain raw material powder, and sintered to obtain silicon nitride ceramic material.

[0057] Among them, by mass percentage, the grinding balls include 60wt% silicon nitride grinding balls and 40wt% zirconium oxide grinding balls. The diameter of the zirconium oxide grinding balls is 1mm, the diameter of the silicon nitride grinding balls is 1mm, and the grinding time is 3h.

[0058] The silicon nitride powder accounts for 85wt% of the premixed powder, the sintering aid accounts for 15wt%, and the mass ratio of the grinding ball to the premixed powder is 1:1.

[0059] The particle size of the silicon nitride powder is 5 μm, and the particle size of the sintering aid is 0.5 μm;

[0060] The particle size of the raw material powder was 0.60 μm.

[0061] The sintering aids are Y2O3 and MgSiN2, the mass ratio of Y2O3 and MgSiN2 is 5:2, and the sintering conditions are: gas pressure sintering at 1850°C and 1MPa N2 pressure for 6h.

[0062] The relative density of the obtained silicon nitride ceramic material is ≥98.8%, and the overall density is 3.26g / cm 3 , thermal conductivity is 120W / (m·K), bending strength is 543MPa, fracture toughness is 7.5MPa·m 1 / 2 .

[0063] Example 3

[0064] The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder;

[0065] The premixed powder is added into a ball mill jar equipped with grinding balls, ball-milled to obtain raw material powder, and sintered to obtain silicon nitride ceramic material.

[0066] Among them, by mass percentage, the grinding balls include 40wt% silicon nitride grinding balls and 60wt% zirconium oxide grinding balls. The diameter of the zirconium oxide grinding balls is 8mm, the diameter of the silicon nitride grinding balls is 2mm, and the grinding time is 2h.

[0067] The silicon nitride powder accounts for 90wt% of the premixed powder, the sintering aid accounts for 10wt%, and the mass ratio of the grinding ball to the premixed powder is 3:1.

[0068] The particle size of the silicon nitride powder is 5 μm, and the particle size of the sintering aid is 1 μm;

[0069] The particle size range of the raw powder is 0.55 μm.

[0070] The sintering aids are Y2O3 and MgSiN2, the mass ratio of Y2O3 and MgSiN2 is 5:2, and the sintering conditions are: hot pressing sintering at 1850°C and 30MPa pressure for 2h.

[0071] The relative density of the obtained silicon nitride ceramic material is ≥99.1%, and the overall density is 3.27g / cm 3 , thermal conductivity is 101W / (m·K), bending strength is 702MPa, fracture toughness is 6.6MPa·m 1 / 2 .

[0072] Example 4

[0073] The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder;

[0074] The premixed powder is added into a ball mill jar equipped with grinding balls, ball-milled to obtain raw material powder, and sintered to obtain silicon nitride ceramic material.

[0075] Among them, by mass percentage, the grinding balls include 70wt% silicon nitride grinding balls and 30wt% zirconium oxide grinding balls. The diameter of the zirconium oxide balls is 2mm, the diameter of the silicon nitride grinding balls is 4mm, and the grinding time is 6h.

[0076] The silicon nitride powder accounts for 92wt% of the premixed powder, the sintering aid accounts for 8wt%, and the mass ratio of the grinding ball to the premixed powder is 2:1.

[0077] The particle size of the silicon nitride powder is 5 μm, and the particle size of the sintering aid is 0.5 μm;

[0078] The particle size range of the raw powder is 0.63 μm.

[0079] The sintering aids are Y2O3 and MgO, the mass ratio of Y2O3 to MgO is 5:2, and the sintering conditions are: gas pressure sintering at 1900°C and 1MPa N2 pressure for 4h.

[0080] The relative density of the obtained silicon nitride ceramic material is ≥98.8%, and the overall density is 3.25g / cm 3 , thermal conductivity is 109W / (m·K), bending strength is 667MPa, fracture toughness is 6.9MPa·m 1 / 2 .

[0081] Example 5

[0082] The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder;

[0083] The premixed powder is added into a ball mill jar equipped with grinding balls, ball-milled to obtain raw material powder, and sintered to obtain silicon nitride ceramic material.

[0084] Among them, by mass percentage, the grinding balls include 50wt% silicon nitride grinding balls and 50wt% zirconium oxide grinding balls. The diameter of the zirconium oxide balls is 2mm, the diameter of the silicon nitride grinding balls is 2mm, and the grinding time is 6h.

[0085] The silicon nitride powder accounts for 88wt% of the premixed powder, the sintering aid accounts for 12wt%, and the mass ratio of the grinding ball to the premixed powder is 4:1.

[0086] The particle size of the silicon nitride powder is 5 μm, and the particle size of the sintering aid is 0.8 μm;

[0087] The particle size range of the raw powder is 0.53 μm.

[0088] The sintering aids are Gd2O3 and MgO, the mass ratio of Gd2O3 to MgO is 7:3, and the sintering conditions are: gas pressure sintering at 1850°C and 1MPa N2 pressure for 6h.

[0089] The relative density of sintered silicon nitride ceramic material is ≥99.5%, and the overall density is 3.27g / cm 3 , thermal conductivity is 115W / (m·K), bending strength is 610MPa, fracture toughness is 7.2MPa·m 1 / 2 .

[0090] Comparative Example 1

[0091] The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder;

[0092] The premixed powder is added into a ball mill jar containing silicon nitride grinding balls, ball milled to obtain raw material powder, and sintered to obtain silicon nitride ceramic material.

[0093] The diameter of the silicon nitride grinding ball is 1 mm, and the grinding time is 3 h.

[0094] The silicon nitride powder accounts for 85wt% of the premixed powder, the sintering aid accounts for 15wt%, and the mass ratio of the grinding ball to the premixed powder is 1:1.

[0095] The particle size of the silicon nitride powder is 5 μm, and the particle size of the sintering aid is 0.5 μm;

[0096] The particle size range of the raw powder is 0.93 μm.

[0097] The sintering aids are Y2O3 and MgSiN2, the mass ratio of Y2O3 to MgSiN2 is 5:2, and the sintering conditions are: gas pressure sintering at 1850°C and 1MPa N2 pressure for 6h.

[0098] The relative density of sintered silicon nitride ceramic material is ≥97.8%, and the overall density is 3.20g / cm 3, thermal conductivity is 87W / (m·K), bending strength is 522MPa, fracture toughness is 7.8MPa·m 1 / 2 .

[0099] Comparative Example 2

[0100] The silicon nitride powder, the sintering aid and the zirconium oxide are mixed in proportion to obtain a premixed powder;

[0101] The premixed powder is added into a ball mill jar containing silicon nitride grinding balls, ball milled to obtain raw material powder, and sintered to obtain silicon nitride ceramic material.

[0102] Among them, the diameter of the silicon nitride grinding ball is 2 mm, and the grinding time is 2 h.

[0103] The premixed powder contains 88wt% silicon nitride powder, 8.8wt% sintering aid, 3.2wt% zirconium oxide, and a mass ratio of grinding balls to premixed powder of 3:1.

[0104] The particle size of the silicon nitride powder is 5 μm, the particle size of the sintering aid is 1 μm, and the particle size of the zirconium oxide powder is 0.5 μm;

[0105] The particle size range of the raw material powder is 1.2 μm.

[0106] The sintering aids are Y2O3 and MgSiN2, the mass ratio of Y2O3 to MgSiN2 is 5:2, and the sintering conditions are: hot pressing sintering at 1850°C and 30MPa pressure for 2h.

[0107] The relative density of sintered silicon nitride ceramic material is ≥98.1%, and the overall density is 3.22g / cm 3 , thermal conductivity is 76W / (m·K), bending strength is 641MPa, fracture toughness is 6.7MPa·m 1 / 2 .

[0108] Comparative Example 3

[0109] The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder;

[0110] The premixed powder is added into a ball mill jar equipped with grinding balls, ball-milled to obtain raw material powder, and sintered to obtain silicon nitride ceramic material.

[0111] Among them, by mass percentage, the grinding balls include 70wt% silicon nitride grinding balls and 30wt% aluminum oxide grinding balls. The diameter of the aluminum oxide balls is 2mm, the diameter of the silicon nitride grinding balls is 4mm, and the grinding time is 6h.

[0112] The silicon nitride powder accounts for 92wt% of the premixed powder, the sintering aid accounts for 8wt%, and the mass ratio of the grinding ball to the premixed powder is 2:1.

[0113] The particle size of the silicon nitride powder is 5 μm, and the particle size of the sintering aid is 0.5 μm;

[0114] The particle size range of the raw powder is 0.85 μm.

[0115] The sintering aids are Y2O3 and MgO, the mass ratio of Y2O3 to MgO is 5:2, and the sintering conditions are: gas pressure sintering at 1900°C and 1MPaN2 pressure for 4h.

[0116] The relative density of sintered silicon nitride ceramic material is ≥98.2%, and the overall density is 3.23g / cm 3 , thermal conductivity is 71W / (m·K), bending strength is 611MPa, fracture toughness is 6.3MPa·m 1 / 2 .

[0117] Data summary table of Examples 1-5 and Comparative Examples 1-3

[0118]

[0119] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A raw material powder for preparing high thermal conductivity silicon nitride ceramics, characterized in that: The raw material powder includes Silicon nitride powder; Sintering aids; as well as Zirconia chips that fall off from zirconia grinding balls when grinding with zirconia grinding balls and silicon nitride grinding balls.

2. The raw material powder according to claim 1, characterized in that: The particle size of the raw material powder is in the range of 0.5-0.8 μm.

3. The method for preparing raw material powder according to claim 1 or 2, characterized in that: The steps include: The silicon nitride powder and the sintering aid are mixed in proportion to obtain a premixed powder; Add the premixed powder into a ball mill containing grinding balls and grind to obtain the product; The grinding balls are composed of silicon nitride grinding balls and zirconium oxide grinding balls. The content of zirconium oxide grinding balls in the grinding balls is 30-60wt%, and the content of silicon nitride grinding balls is 40-70wt%.

4. The preparation method according to claim 3, characterized in that: The particle size of the zirconium oxide grinding ball is 0.5-12 mm, and the particle size of the silicon nitride grinding ball is 1-4 mm.

5. The preparation method according to claim 3, characterized in that: The particle size of the silicon nitride powder is in the range of 5-7 μm, and the particle size of the sintering aid is in the range of 0.1-1.0 μm.

6. The preparation method according to claim 3, characterized in that: The silicon nitride powder in the premixed powder accounts for 85-95wt%, the sintering aid accounts for 5-15wt%, and the total mass percentage of the silicon nitride powder and the sintering aid is 100wt%; The mass ratio of the grinding balls to the premixed powder is 1-4:

1.

7. The preparation method according to claim 1, characterized in that: The sintering aid is selected from one or more of Y2O3, Sc2O3, Sm2O3, Lu2O3, Er2O3, MgO, Mg2Si and MgSiN2.

8. A high thermal conductivity silicon nitride ceramic, characterized in that: The raw material powder as claimed in any one of claims 1 or 2 is sintered to obtain the product.

9. The high thermal conductivity silicon nitride ceramic according to claim 8, characterized in that: The relative density of the high thermal conductivity silicon nitride ceramic is ≥98%, and the overall density is 3.20-3.31 g / cm 3 , thermal conductivity is 100-120W / (m·K), bending strength is 500-780MPa, fracture toughness is 6.0-8.5MPa·m 1 / 2 .

10. Use of the high thermal conductivity silicon nitride ceramic according to any one of claims 8 or 9 in preparing thermal conductive materials.

Citation Information

Patent Citations

  • A silicon nitride ceramic material with high thermal conductivity and high strength and its preparation method

    CN108863395B

  • High-thermal-conductivity silicon nitride ceramic material and preparation method thereof

    CN111196727A

  • Ball milling method for improving particle size and particle size distribution of silicon nitride powder

    CN109650904A

  • Silicon nitride sintered bodies and a method for producing the same

    US4535063A

Cited By

  • Silicon nitride ceramic and preparation method thereof

    CN121651943A